Development of Instruments to Measure Automotive Electrical Competency - Heru Arizal; Suparji Suparji; Marniati Marniati; Revi Safitri; Yuli Sutoto Nugroho (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Competence is an individual's ability to do a job adequately and appropriately. Competence is needed in the field of work. Future vehicles are currently heading towards electric-based vehicles. Therefore, graduates who have competence, especially in electricity, are needed. Valid and accurate measuring instruments are needed to determine a person's competence. Therefore, in this study, instruments were developed to measure student competence in automotive electricity. Method: The research method used is a development study using a 4D model consisting of four phases: Defining, Designing, Developing, and Disseminating. The finished instrument is validated and tested to see its validity and reliability. Results: This study obtained automotive electrical competency instruments in 3 instruments, namely to measure knowledge, skills, and attitudes. There is 1 question item that must be dropped because the CVR value and correlation test items are below 0.3, and the outfit and infit values are above 2. No question items are dropped for instruments, indicators, attitudes, and skills. All automotive electrical competency instruments produce reliable instruments. Novelty: a unique instrument that focuses on automotive electrical competence. This approach includes knowledge, skills, and attitudes towards technological developments.